2008
DOI: 10.7205/milmed.173.5.422
|View full text |Cite
|
Sign up to set email alerts
|

Longer-Term Career Outcomes of Uniformed Services University of the Health Sciences Medical School Graduates: Classes of 1980–1989

Abstract: Many accomplishments, to include high sustained board certification rates from a diverse array of specialties, broad deployment experience, achievement of high leadership responsibilities and senior rank, as well as important contributions to academic medicine were achieved by these graduates. Our results support that USUHS is accomplishing its societal charge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This information is gathered and evaluated as part of the university’s Long-Term Career Outcome Study. 15 , 16 Leadership elements in the database include student demographic information as well as performance during pre-clerkship, clerkship phases of education, and beyond. The merging of these data sets allows for evaluation of leadership performance in relationship to individual differences and medical professional performance.…”
Section: Introductionmentioning
confidence: 99%
“…This information is gathered and evaluated as part of the university’s Long-Term Career Outcome Study. 15 , 16 Leadership elements in the database include student demographic information as well as performance during pre-clerkship, clerkship phases of education, and beyond. The merging of these data sets allows for evaluation of leadership performance in relationship to individual differences and medical professional performance.…”
Section: Introductionmentioning
confidence: 99%
“…HPSP students are far less likely to spend a career in the military than are USU students. 15 This may bring financial aspects to the forefront for these students in their specialty choice. Downloaded by [141.214.17.222] at 20:19 04 November 2014…”
Section: Discussionmentioning
confidence: 99%
“…One study in 2008 showed that USUHS graduates completed residencies mostly in surgery, family medicine, internal medicine, and pediatrics. Four percent of graduates completed a residency in emergency medicine (12).…”
Section: Postgraduate Education In the Militarymentioning
confidence: 99%